2020
DOI: 10.1016/j.ijhydene.2020.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of pure and milled Mg17Al12 in “model” seawater solution

Abstract: h i g h l i g h t s Mg 17 Al 12 corrodes in a 3.5 wt% aqueous solution of NaCl with a corrosion current density of 5.3 mA/cm 2 . Mg 17 Al 12 can act as cathode in Mg Al alloy with an OCP of 1.2 V/SCE. Electrochemical impedance spectroscopy can explain the effect of ball milling additives. Ball milling with MgCl 2 increases the corrosion current density by 22 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The vertical tip-substrate distance was first adjusted through Z-approach curves using feedback mode in an absolute ethanol solution while the electrochemical reactivity of the surface was investigated by collecting the generated H2 in NaCl solution. Measurements carried out on pure Mg and pure Mg17Al12 confirmed the previously reported results on the corrosion of each of the two materials [41,42,54]. The effect of galvanic coupling on the corrosion behavior of both Mg and Mg17Al12 was clarified through SECM mapping of "Mg+Mg17Al12" material with the same composition of AZ91 (apart from the presence of 1 wt.% of Zn) but with a controlled microstructure [42].…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…The vertical tip-substrate distance was first adjusted through Z-approach curves using feedback mode in an absolute ethanol solution while the electrochemical reactivity of the surface was investigated by collecting the generated H2 in NaCl solution. Measurements carried out on pure Mg and pure Mg17Al12 confirmed the previously reported results on the corrosion of each of the two materials [41,42,54]. The effect of galvanic coupling on the corrosion behavior of both Mg and Mg17Al12 was clarified through SECM mapping of "Mg+Mg17Al12" material with the same composition of AZ91 (apart from the presence of 1 wt.% of Zn) but with a controlled microstructure [42].…”
Section: Introductionsupporting
confidence: 82%
“…This paper discusses the effect of the interaction between Mg and Mg17Al12 and their behavior during the corrosion process. Previous studies on the corrosion behavior of pure Mg17Al12 in NaCl solution (where Clanions favor the formation of water-soluble MgCl2 inhibiting the formation of Mg(OH)2 passive layer) [40,41] confirmed that a galvanic coupling between Mg and Mg17Al12 exist and that "global" corrosion of Mg17Al12 is slower than that of Mg. The effect of the galvanic coupling between these two phases was studied indirectly through several AZ91 model materials where the microstructures of the materials can be controlled.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The experimental setup is detailed in reference. 22 Hydrogen production is presented both as gas volume generation (in mL) and as the conversion yield (%). This latest is defined as the volume of produced hydrogen over the theoretical volume (when all the hydrogen from PMHS and KOH is completely consumed).…”
Section: Hydrogen Generation Kinetic Experimentsmentioning
confidence: 99%